Evaluation of the therapeutic safety of beta-blockers in acute heart failure in hospital emergency (Research, Society and Development, 2023)
Beta-blockers are essential drugs for the treatment of Chronic Heart Failure (HF), and their use for heart rate (HR) control in acute HF was not properly standardized due to the association with serious adverse effects. However, recent studies suggest that the use of these drugs can reduce morbidity and mortality rates generated in acute HF. Thus, the objective of this study is to evaluate the safety of beta-blockers in patients hospitalized for acute heart failure in the hospital emergency department. This is an integrative literature review carried out between January and June 2023 based on the PubMed and BVS databases. At the end of the selection, 13 studies were analyzed, including randomized clinical trials, prospective, retrospective and ambispective studies, case reports and systematic review, in which the clinical safety of various beta-blockers was demonstrated with a significant reduction in morbidity and mortality rates and low rates of associated adverse effects in patients with acute HF and good peripheral perfusion, but its use is still proscribed in patients with low output profiles. Therefore, beta-blockers, especially caverdilol and landiolol, are recommended for controlling HR in patients with acute HF and good perfusion, as they reduce morbidity and mortality rates and readmissions resulting from these conditions.